Influence of Climate on Clinical Diagnostic Dry Eye Tests: Pilot Study. Issue 9 (September 2015) - Tesón, Marisa; López-Miguel, Alberto; Neves, Helena; Calonge, Margarita; González-García, María J.; González-Méijome, José M.
ABSTRACT: Purpose: To analyze dry eye disease (DED) tests and their consistency in similar nonsymptomatic population samples living in two geographic locations with different climates (Continental vs. Atlantic). Methods: This is a pilot study including 14 nonsymptomatic residents from Valladolid (Continental climate, Spain) and 14 sex-matched and similarly aged residents from Braga (Atlantic climate, Portugal); they were assessed during the same season (spring) of two consecutive years. Phenol red thread test, conjunctival hyperemia, fluorescein tear breakup time, corneal and conjunctival staining, and Schirmer test were evaluated on three different consecutive visits. Reliability was assessed using the intraclass correlation coefficient and weighted kappa ( κ ) coefficient for quantitative and ordinal variables, respectively. Results: Fourteen subjects were recruited in each city with a mean (±SD) age of 63.0 (±1.7) and 59.1 (±0.9) years (p = 0.08) in Valladolid and Braga, respectively. Intraclass correlation coefficient and κ values of the tests performed were below 0.69 and 0.61, respectively, for both samples, thus showing moderate to poor reliability. Subsequently, comparisons were made between the results corresponding to the middle and higher outdoor relative humidity (RH) visit in each location as there were no differences in mean temperature (p ≥ 0.75) despite RH values significantly differing (p ⩽ 0.005). Significant (p ⩽ 0.05) differences were observed between Valladolid and Braga samples on tear breakup time (middle RH visit, 2.76 ± 0.60 vs. 5.26 ± 0.64 seconds; higher RH visit, 2.61 ± 0.32 vs. 5.78 ± 0.88 seconds) and corneal (middle RH, 0.64 ± 0.17 vs. 0.14 ± 0.10; higher RH, 0.60 ± 0.22 vs. 0.0 ± 0.0) and conjunctival staining (middle RH, 0.61 ± 0.17 vs. 0.14 ± 0.08; higher RH, 0.57 ± 0.15 vs. 0.18 ± 0.09). Conclusions: This pilot study provides initial evidence to support that DED test outcomes assessing the ocular surface integrity and tear stability are climate dependent. Future large-sample studies should support these outcomes also in DED patients. This knowledge is fundamental for multicenter clinical trials. Lack of consistency in diagnostic clinical tests for DED was also corroborated.